Intensive care needs and predictors of mortality in critical pertussis: A single center experience - T K Kavitha; Madhusudan Samprathi; Namita Ravikumar; Muralidharan Jayashree; V Gautam; N Jain; R Kumar; A Bansal; A Baranwal; N Karthi; S Verma; Lucky sangal (Wolters Kluwer Medknow Publications, 2018)
Objective: To study the clinical profile, intensive care needs and predictors of mortality in critical pertussis. Material and methods: Case records of 36 children >1 month to 5 years old with probable critical pertussis admitted to a tertiary care PICU of a teaching and referral hospital between January 2016 and May 2018 were analyzed retrospectively. Clinical, laboratory and treatment variables between survivors and nonsurvivors were compared to determine predictors of mortality. Results: Subjects included 21(58.5%) boys and 15 (41.7%) girls. The median (IQR) age was 3.5 (1.5,7) months. Typical paroxysmal cough 31 (86.1%), apnea 15 (41.7%) and seizures 17 (47.2%) were presenting symptoms. Twenty-one (58.3%) children were unimmunized for pertussis. Twenty-three were pertussis PCR positive. Respiratory failure (n=35, 97.2%), and hyperleukocytosis (n= 22, 61.1%) were major complications. Intensive care needs included mechanical ventilation (n=11, 30.6%), vasoactive support (n=7, 19.4%) and exchange transfusion (n=3, 8.3%). Pulmonary arterial hypertension (PAH) was detected in 5 out of 15 (33.3%) children who underwent echocardiography. Eight (22.2%) children died during PICU stay. Median (IQR) length of PICU stay in survivors was 4 (3, 5) days. On univariate analysis, female sex, apnea, hyperleukocytosis, encephalopathy (GCS< 14), need for vasoactive support and mechanical ventilation predicted mortality. Conclusions: There is a resurgence of pertussis. Infants before starting or completion of their primary immunization schedule are at high risk for critical pertussis. Hyperleukocytosis, need for vasoactive support and mechanical ventilation were predictors of poor outcome.